2017
DOI: 10.1016/j.tsf.2017.06.057
|View full text |Cite
|
Sign up to set email alerts
|

Controlling refractive index in AlN films by texture and crystallinity manipulation

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…In addition to high refractive index, AlN has the characteristic of high transmittance. Many literatures [26][27][28] reported that AlN films with more than 80% transmittance in visible band can be obtained by DC magnetron sputtering technology. AlN films with high refractive index and light transmittance have excellent properties for optoelectronic applications, such as solar cell protective coatings [26] and heat dissipation material for high power lighting devices [29].…”
Section: Resultsmentioning
confidence: 99%
“…In addition to high refractive index, AlN has the characteristic of high transmittance. Many literatures [26][27][28] reported that AlN films with more than 80% transmittance in visible band can be obtained by DC magnetron sputtering technology. AlN films with high refractive index and light transmittance have excellent properties for optoelectronic applications, such as solar cell protective coatings [26] and heat dissipation material for high power lighting devices [29].…”
Section: Resultsmentioning
confidence: 99%
“…More details can be found in ref. 24 The samples underwent a post-deposition rapid thermal annealing (RTA) at shows some random local structure disorder that may be due to incorporation of Ce ions. This local disorder in the microstructure leads to significant microstrain, as reported in.…”
Section: Methodsmentioning
confidence: 99%
“…Texture, which describes the statistical distribution of grain orientations, is an important microstructural characteristic of thin films, as it can strongly influence the various functional properties [1][2][3][4][5][6][7][8][9][10]. Four types of texture component have been identified in thin films: random texture, in which the orientations of grains are fully random (no preferred growth orientation); fiber texture [1,11,12], where the orientation of a lattice plane is preferentially parallel to the substrate plane, while there is some rotational degree of freedom around the axis perpendicular to the substrate plane; in-plane texture (epitaxy), in which all three axes of the grains in thin film are aligned and fixed by the crystallographic orientations of single crystal substrates [1,11,13,14];…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the degree of preferred orientation was estimated quantitatively by calculating Harris texture coefficient (T c ), following subtraction of background. T c is defined as[9,23,24]:…”
mentioning
confidence: 99%